Reactive stroma in the prostate during late life: The role of microvasculature and antiangiogenic therapy influences. Issue 14 (17th July 2015) - Montico, Fabio; Kido, Larissa Akemi; San Martin, Rebeca; Rowley, David R.; Cagnon, Valéria H. A.
<x xml:space="preserve">Abstract</x> BACKGROUND Prostate cancer is associated to a reactive stroma microenvironment characterized by angiogenic processes that are favorable for tumor progression. Senescence has been identified as a predisposing factor for prostate malignancies. In turn, the relationships between aging, reactive stroma, and the mechanisms that induce this phenotype are largely unknown. Thus, we investigated the occurrence of reactive stroma in the mouse prostate during advanced age as well as the effects of antiangiogenic and androgen ablation therapies on reactive stroma recruitment. METHODS Male mice (52‐week‐old FVB) were treated with two classes of angiogenesis inhibitors: direct (TNP‐470; 15 mg/kg; s.c.) and/or indirect (SU5416; 6 mg/kg; i.p.). Androgen ablation was carried out by finasteride administration (20 mg/kg; s.c.), alone or in association to both inhibitors. The Transgenic Adenocarcinoma of the Mouse Prostate (TRAMP) model was used as a paradigm of cancer‐associated reactive stroma. The dorsolateral prostate was collected for α‐actin (αSMA), vimentin (VIM), and transforming growth factor‐beta (TGF‐β) immunohistochemical and Western blotting analyses as well as for CD34/αSMA and CD34/VIM colocalization. RESULTS Senescence was associated with increased αSMA, VIM, and TGF‐β expression as well as with the recruitment of CD34/αSMA and CD34/VIM dual‐positive fibroblasts. These observations were similar to those verified in TRAMP mice. Antiangiogenic treatment promoted the recovery of senescence‐associated stromal changes. Hormonal ablation, despite having led to impaired CD34/αSMA and CD34/VIM dual‐positive cell recruitment, did not result in decreased stimulus to reactive stroma development, due to enhanced TGF‐β expression in relation to the aged controls. CONCLUSIONS Reactive stroma develops in the prostate of non‐transgenic mice as a result of aging. The periacinar microvasculature is a candidate source for the recruitment of reactive stroma‐associated cells, which may be derived either from perivascular‐resident mesenchymal stem cells (MSCs) or from an endothelial‐to‐mesenchymal transition (EndMT) process. Thus, antiangiogenic therapy is a promising approach for preventing age‐associated prostate malignancies by means of its negative interference in the development of reactive stroma phenotype from the vascular wall. Prostate 75:1643–1661, 2015. © 2015 Wiley Periodicals, Inc.